Note about the " Survey of current inflationary and deflationary tendencies" prepared by the United Nations department of economic affairs - PIETRANERA, G. (PSL Quarterly Review, 2014)
The article critically examines a recent publication of the United Nations’ Department of Economic Affairs. The author considers some of the statistical material concerning inflation in Italy and discusses the unusual coincidence of this inflation with widespread unemployment, which the Survey regards as a particular and exceptional case. JEL: E24, E31, F53